1997
DOI: 10.1103/physrevd.55.r7340
|View full text |Cite
|
Sign up to set email alerts
|

New scenario for the early evolution of the Universe

Abstract: We propose that the Universe was created from ''nothing'' with a relatively small number of particles and quickly relaxed to a quasiequilibrium state at the Planck parameters. The classic cosmological solution for this Universe with a ⌳ term has two branches divided by a gap. The quantum process of tunneling between the cosmological solution branches and kinetics of the second order relativistic phase transition in a supersymmetric SU͑5͒ model on GUT scale are investigated using numerical methods. The Einstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The Universe has emerged as a result of a tunneling process after a bounce from a singularity in the presence of oscillations, and further arrived at a Friedmann regime through a quantum regime [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Universe has emerged as a result of a tunneling process after a bounce from a singularity in the presence of oscillations, and further arrived at a Friedmann regime through a quantum regime [32].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not know exactly how our Universe lost its high degree of symmetry. The elementary chain of phase transitions written [32], of which only the two last ones can be calculated precisely in the frame of Standard Model, is:…”
Section: Phase Transitions (Quantum Regime)mentioning
confidence: 99%
“…The idea of a similarity of the thermodynamics of a black hole in special coordinates to the thermodynamics of a de Sitter Universe belonging to S. Hawking [21] turned out to be very useful, as did T. Jacobson's idea [22] that gravity on the macroscopic scale is a manifestation of vacuum thermodynamics. Our Universe, after its creation [2], passed the quantum stage of its evolution, when holographic ideas can not used, since holography is a classical phenomenon. Probably, in the quantum regime our Universe lost its high symmetry, extra dimensions, and parity, but at the same time, a whole bunch of particles, including the dark ones, was produced.…”
Section: Dark Energymentioning
confidence: 99%
“…A. Friedman [14] showed that the static solutions of the Einstein's equation (1) Here, we have a difference in vacuum energy density by 123 orders of magnitude that were reduced through rather ordinary physical processes during the evolution of the Universe. Our Universe was probably born by tunneling from an oscillating regime to the Friedmann one [2] and began to expand. New microstates arise during its expansion (evolution).…”
Section: Dark Energymentioning
confidence: 99%
See 1 more Smart Citation